Dosimetric evaluation of high-Z inhomogeneity used for hip prosthesis: A multi-institutional collaborative study. (March 2022) - Yadav, Poonam; Chang, Sha X.; Cheng, Chee-Wai; DesRosiers, Colleen M.; Mitra, Raj K.; Das, Indra J.
Highlight: High-Z inhomogeneities are more prevalent in older patients and dosimetry is uncertain. This study compares dose calculation algorithms from various treatment planning systems. It compares with dose calculation and measurements in a real hip prosthesis. Provides guidelines for dosimetry. Abstract: Purpose: A multi-institutional investigation for dosimetric evaluation of high-Z hip prosthetic device in photon beam. Methods: A bilateral hip prosthetic case was chosen. An in-house phantom was built to replicate the human pelvis with two different prostheses. Dosimetric parameters: dose to the target and organs at risk (OARs) were compared for the clinical case generated by various treatment planning system (TPS) with varied algorithms. Single beam plans with different TPS for phantom using 6 MV and 15 MV photon beams with and without density correction were compared with measurement. Results: Wide variations in target and OAR dosimetry were recorded for different TPS. For clinical case ideal PTV coverage was noted for plans generated with Corvus and Prowess TPS only. However, none of the TPS were able to meet plan objective for the bladder. Good correlation was noticed for the measured and the Pinnacle TPS for corrected dose calculation at the interfaces as well as the dose ratio in elsewhere. On comparing measured and calculated dose, the difference across the TPS varied from −20% to 60% for 6 MV and 3% to 50% for the 15 MV, respectively. Conclusion: Most TPS do not provide accurate dosimetry with high-Z prosthesis. It is important to check the TPS under extreme conditions of beams passing through the high-Z region. Metal artifact reduction algorithms may reduce the difference between the measured and calculated dose but still significant differences exist. Further studies are required to validate the calculational accuracy.